2021
DOI: 10.36366/frontiers.v33i2.534
|View full text |Cite
|
Sign up to set email alerts
|

An Intersectional Investigation of Study Abroad Intent among Latino/a and White First-generation College Students

Abstract: Despite a marked increase in study abroad participation in recent decades, first-generation students and Students of Color remain vastly underrepresented.  The current study sought to expand the extant literature on first-generation and Latino/a students’ study abroad participation by applying an intersectional approach to identifying predictors of study abroad intent.  A total of 478 undergraduates (Latino/a and White; first-generation and continuing-generation) completed a questionnaire based on previously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Though fewer in number, some research has focused on the perceptions and experiences of the Latinx community with regard to education abroad. In addition to financial concerns, several studies suggested that students from immigrant backgrounds may be less intrigued by travel to another country to study and learn about another culture since they navigate different cultures in their everyday lives (Goldstein & Lopez, 2021;Orb, 2004). Indeed, a study comparing Latinx and first-generation White students' intent to study abroad with that of continuinggeneration White students found that characteristics such as adventurousness and language interest were much more important to continuing generation (CG) White students than the other two groups (Goldstein & Lopez, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Though fewer in number, some research has focused on the perceptions and experiences of the Latinx community with regard to education abroad. In addition to financial concerns, several studies suggested that students from immigrant backgrounds may be less intrigued by travel to another country to study and learn about another culture since they navigate different cultures in their everyday lives (Goldstein & Lopez, 2021;Orb, 2004). Indeed, a study comparing Latinx and first-generation White students' intent to study abroad with that of continuinggeneration White students found that characteristics such as adventurousness and language interest were much more important to continuing generation (CG) White students than the other two groups (Goldstein & Lopez, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to financial concerns, several studies suggested that students from immigrant backgrounds may be less intrigued by travel to another country to study and learn about another culture since they navigate different cultures in their everyday lives (Goldstein & Lopez, 2021;Orb, 2004). Indeed, a study comparing Latinx and first-generation White students' intent to study abroad with that of continuinggeneration White students found that characteristics such as adventurousness and language interest were much more important to continuing generation (CG) White students than the other two groups (Goldstein & Lopez, 2021). Other studies have found that Latinx students are just as interested in education abroad as their White counterparts, but they tend to delay international travel to after college because of a desire to remain near family and not delay individual graduation deadlines (McClure et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Latinx students in particular may have different family expectations and experiences that make going abroad feel unattainable, or it may be something no one has helped them consider as a viable possibility. Obstacles to participating in study abroad programs that many Latinx students face include: lack of exposure to study abroad, concerns about degree completion, family obligations and influence, anticipated discrimination, lack of personally relevant programs, and exclusionary marketing practices (Goldstein & Lopez, 2021). In addition to these barriers, Latinx students are also more likely to have off-campus jobs during the school year and to work longer hours than their White peers in order to assist with family expenses and/or to finance their education (Martin, 2015;McClure et al, 2010;Pascarella et al, 2004;Tolan & McCullers, 2018).…”
Section: Study Abroad: What It Should Do For Students and Communitiesmentioning
confidence: 99%
“…Negotiating multiple layers of identity is central to first-generation students' ability to move between the requirements of home and school environments. Such cultural navigational skills are valuable in study abroad experiences which require students to interact with individuals who differ from themselves on multiple dimensions (Goldstein & Lopez, 2021). Additionally, Wick et al (2019) found that Latinx students studying in Costa Rica were able to take advantage of their pre-existing strengths through familial, aspirational, linguistic, and resistant capital to frame and enhance their abroad experience.…”
Section: Study Abroad: What It Should Do For Students and Communitiesmentioning
confidence: 99%
“…The research base on study abroad is multidisciplinary and includes a range of outcomes, including intercultural awareness, language acquisition, academic content learning, and wellbeing (Brunsting et al, 2023;Miller-Perrin & Thompson, 2014;Twombly et al, 2012;Varela, 2017). Currently, there is increased interest in examining the relationship between identity and study abroad outcomes (AIEA, 2021), with a strong emphasis on students of color (Sweeney, 2013), first-generation college students (Goldstein & Lopez, 2021), and gender (Salisbury et al, 2010). By examining identity, study abroad practitioners and scholars may achieve a more nuanced understanding of students' experiences and development during study abroad.…”
Section: Introductionmentioning
confidence: 99%